The effect of muscular strength and strength asymmetry on jumping height in soccer players - Misjuk, M.; Rannama, I. (Isokinetics and Exercise Science, 2022)
BACKGROUND: Lower limb muscular asymmetry is not well studied and may have a negative impact on performance. OBJECTIVE: To estimate how muscular strength and strength asymmetry affect jumping performance in soccer players. METHODS: Twenty-eight male professional soccer players took part in the study. The countermovement jump (CMJ) without arm swing was used to determine jumping height. Muscle strength was measured concentrically at 60 and 300°/s. RESULTS: The peak moment of the knee extensors was positively and significantly correlated with the CMJ; r= 0.608 at 300°/s and r= 0.489 at 60°/s. The asymmetry of the knee flexors between the stronger and weaker leg was negatively and moderately correlated with the CMJ at 300°/s (r=-0.396). The regression model (R2= 0.474) showed that an increase of 0.18-Nm/kg in the relative strength of the knee extensors at 300°/s (by one SD) was related to an increase of 3-cm in the CMJ. Reducing the asymmetry of the knee flexors by 6.8 percentage points (by one SD) was related to a rise of 1.7-cm in the CMJ. CONCLUSIONS: Greater strength in the knee extensors, preferably tested at higher velocity, and reduced asymmetry in the strength of the lower hamstring muscles have a statistically significant effect on the CMJ.